The effects of a video game on student performance in the knowledge test in the discipline "Professional Practice and Ethics in Physiotherapy" from the University of Brasilia - Ana Clara Bonini Rocha; Jorge Luís Barreto Pereira; Caio Felipe Teixeira Soares; Priscilla Barbosa; Amanda Cindy da Silva; André Marques de Moraes; Wagner Rodrigues Martins (Universidade Estadual de Campinas, 2017)
The current study aimed the evaluation of the long term effect of the educational video game (EVG) in the specific knowledge test (SKT) performance, opinion of satisfaction with the discipline (OSD) and learning perception of the subject matter (LP) of a graduation discipline in the Physiotherapy course of the Universidade de Brasília (UnB). This study is a randomized clinical trial with two groups: Experimental Group (EG): presential classes with extra class use of the EVG; Control Group (CG): only presential classes. Classes occurred once a week with the presence of both groups. Students allocated in EG accessed the EVG platform at least once a week. After 17 weeks the assessment tools were applied for the dependent variables: (I) SKT, (2) OSD, (3) LP. The Student t test was used to compare the SKT means between groups and absolute and relative frequencies were used to report SOD and LP scales. Data was analyzed with significance level of 5%. The sample consisted of a total of 71 students (22,83 [±3,35] years), composed by 62 female (87,3%) and 09 male (12,7%) individuals. There was significant statistical difference between EG and CG in SKT (p=0.006), with EG having higher means than CG. Regarding the secondary endpoints, EG had 100% answers in categories 4 and 5, while GC also showed responses in category 3. Results points that the EVG improved the performance in SKT. The opinion results indicate that the use of the EVG can increase the satisfaction with the discipline and LP.